The Routledge companion to practicing anthropology and design
1 online resource (xx, 419 pages)
Keywords: "The Routledge Companion to Practicing Anthropology and Design provides a comprehensive overview of the history of the relationship between these two fields and their current state, outlining key concepts and current debates as well as positing directions for future practice and research. Bringing together original work from a diverse group of established and emerging professionals, this volume joins a wider conversation about the trajectory of this transdisciplinary movement and inspired by the continuing evolution of Anthropology and Design as they have adapted to accelerating and unpredictable conditions in arenas that span sectors, economies, socio-cultural groups, and geographies. It homes in on both the growing convergence and tensions between them, while exploring how individuals from both fields have found ways of mixing, experimenting, and evolving theory and new forms of practice, highlighting the experimental theories and practices their transdisciplinarity has generated. The Routledge Companion to Practicing Anthropology and Design is a valuable reference tool for practitioners, scholars, and upper-level students in the fields of Anthropology and Design, as well as related disciplines"--